Kill train - Cuartero-Briggs, Olivia (Mad Cave Studios, 2025)
To control the population explosion that nearly crippled the city, New York has instituted Kill Train, a randomized, extermination program where designated subway trains are picked at random, and all the passengers are slaughtered by the end of the line. In this not-so-distant future, we meet Vanessa, a struggling single mom in the midst of a nervous breakdown, who discovers that she, herself, is on a Kill Train. Now, for once in her life and with everything to prove, Vanessa decides she's not going down without a fight.